Evaluation of state sustainable transportation performances (SSTP) using sustainable indicators. (November 2017) - Naganathan, Hariharan; Chong, Wai K.
Highlights: The intents of most of the rating system and certification tools do not focus on measuring the actual sustainability impacts. State Sustainable Transportation Performance (SSTP) matrices evaluate the transportation sustainability of states. SSTP lays down the fundamentals of determining sustainability intents, and quantification approaches. SSTP is not a rating system but a matrix to evaluate the sustainability of transportation policies and systems. Abstract: Transportation systems facilitate the flow of goods and services globally, creating jobs and encouraging economic growth while generating negative impacts on the environment and society. Federal and state transportation agencies rely on sustainable practices to alleviate these impacts. While these practices are critical to lessen these negative impacts, transportation agencies and private companies still face two key challenges: a) understanding and defining the intents of the sustainable practices; and b) quantifying and determining the effectiveness of the practices. The paper addresses the issues of "intents" and "quantification" through the proposed State Sustainable Transportation Performances (SSTP) matrices. SSTP lays down the fundamentals of determining sustainability intents, and quantification approaches through 1) identifying the importance of sustainable indicators that are relevant to the practices and agencies, and 2) analyzing the effectiveness of practices through these indicators. These effectiveness measures could be used to determine the performance of different states' transportation sustainability, and thus understand the gaps of reduced impacts between planned and reality. SSTP is not a rating system but a matrix to evaluate the sustainability of transportation policies and systems.